CFD and exergy analysis of subcritical/supercritical CO2 based naturally circulated solar thermal collector. (April 2022) - Biradar, Madagonda K.; Parmar, Dipal N.; Yadav, Ajay Kumar
Abstract: Solar water heating system is inefficient during winter due to the chances of water freezing and higher viscosity at low temperatures. Several investigations are being done to increase the efficiency of the solar water heater using various secondary fluids for different climatic conditions. This paper emphasises on the study of heat transfer and fluid flow behavior of CO2 based naturally circulated indirect solar water heating system. Subcritical (liquid and vapour) and supercritical CO2 are considered as loop fluid, and the results are compared with water based system. Three-dimensional computational fluid dynamics simulations are carried out for two different weather conditions i.e., winter (278 K) and summer (305 K). Results are obtained for 33° collector inclination angle from horizontal at various operating pressures 50–70 bar for subcritical and 80–100 bar for supercritical CO2 . The CO2 based system yields very high Reynolds number (subcritical liquid: ∼160 times; subcritical vapour: ∼204 times; supercritical vapour: ∼260 times) and very high Nusselt number (subcritical liquid: ∼14 times; subcritical vapour: ∼19.5 times; supercritical vapour: ∼48 times) compared to water based system. Supercritical CO2 based system exhibits 12% higher energy efficiency compared to water. Whereas, subcritical vapour based system exhibits 140% higher exergy efficiency relative to water based system. Graphical abstract: Schematic of a CO2 based naturally circulated solar water heating system. Image 1